UNDERSTANDING OF ZAKAT AS A FORM OF WOMEN'S EMPOWERMENT THROUGH THE ROLE OF FATAYAT NU AT KABUPATEN JEMBER - Qur’ani, Gilang Lita; Indrianti, Deditiani Tri; Ariefianto, Lutfi (Universitas Pendidikan Indonesia (UPI), 2022)
The understanding of zakat in Islam is very important for everyone, especially a woman. Women have a vital role in the family as a companion to their husbands and also as educators for their children in the future. A good literacy and understanding of zakat is one of the muzakki factors in making decisions to pay zakat, both zakat fitrah and zakat maal. In addition, the understanding of zakat is also a symbol of empowerment. This study used a purposive area technique to determine the place,, namely the Fatayat NU Organization Branch Level of Jember Regency. The researcher used purposive sampling technique to determine the informant of this study, then the technique of obtaining data from informants used the snowball sampling technique. The data collection technique used are observation, interviews and documentation. Then, the validity of the data were checked by participation extension, increased persistence, and triangulation. The data were analyzed by pre-field analysis and field analysis. The results illustrate that Fatayat women have understood the concept of zakat in general from their perspective in terms of muzakki, mustahiq and institutional aspects. However, the understanding of zakat maal still needs to be socialized again to the community. The Fatayat NU organization has a role in providing the access, the awareness and the participation regarding the zakat to women. The existence of the structure in economic, social and da'wah fields has a great potential if the education and understanding of zakat is used as an empowerment program. So that, it can create a zakat literate society.